Is hepatitis C virus a cause of idiopathic dilated cardiomyopathy? A systematic review of literature - Reis,Francisco José Farias Borges dos (2006)
Recent studies have suggested that some patients with idiopathic dilated cardiomyopathy (IDC) are also afflicted with insidious forms of viral myocarditis. Participation of hepatitis C virus (HCV) in this process has been postulated. The objective of this study was to evaluate a possible association between hepatitis C virus and idiopathic dilated cardiomyopathy. Systematic review of the literature using electronic databases (MEDLINE, EMBASES, LILACS and COCHRANE) for the period from 1995 to 2005, limited to papers published in English, Spanish and Portuguese. Sixty-two papers were found, of which six were in accordance with the proposed methodology. After selection, the articles were classified by quality of data and number of variables studied. Most of the patients were male adults from 31 and 75 years old, who had ischemic cardiopathy excluded as etiology of the dilated cardiomyopathy. A significant association between dilated cardiomyopathy and hepatitis C virus was found in only two papers, both from Japan and by the same author. Most of the papers received low classifications, as they did not fulfill the systematization criteria.